Explore the Students' Perceptions, Experiences, and Feedback Regarding the Integration of Soft Skills and Language Learning (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The importance of students acquiring soft skills is growing in today's more global industry. Employers nowadays are looking for graduates with strong soft skills as well as hard ones. Soft talents, as opposed to hard skills, are becoming increasingly important to certain firms. Most courses naturally include soft skills, which are useful for students who aren't technically minded. The situation may be different, however, for students majoring in technical fields. Their curriculum is heavily focused on practical skills. As a result, fewer pupils understand the value of soft skills. The research team behind this study hopes to learn how engineering students feel about the value of soft skills. The sample for this study consists of 150 engineering students from the University of Kuala Lumpur's Malaysia France Institute. Though they disagreed on the relative importance of the various components, students generally agreed that teachers played a crucial role and that they improved their cultural awareness, reading and listening comprehension, and ability to work independently. The data is collected via a questionnaire. The findings indicate that students are aware of the importance of soft skills for both their academic performance and their future careers. Two approaches that have been suggested as ways to help students develop their soft skills include problem-based learning and incorporating entrepreneurial elements into technical subjects.